Trauma-informed practices with children and adolescents - Steele, William; Malchiodi, Cathy A. (New York : Routledge, 2012)
"Trauma-Informed Practices with Children and Adolescents is a sourcebook of practical approaches to working with children and adolescents that synthesizes research from leading trauma specialists and translates it into easy-to-implement techniques. The approaches laid out address the sensory and somatic experiences of trauma within structured formats that meet the "best practices" criteria for trauma informed care: safety, self-regulation, trauma integration, healthy relationships, and healthy environments. Each chapter contains short excerpts, case examples, and commentary relevant to the chapter topic from recognized leaders in the field of trauma intervention with children and adolescents. In addition to this, readers will find chapters filled with easily applied activities, methods, and approaches to assessment, self-regulation, trauma integration, and resilience-building. The book's structured yet comprehensive approach provides professionals with the resources they need to help trauma victims not just survive but thrive and move from victim thinking to survivor thinking using the current best practices in the field"--Provided by publisher.
What is trauma informed practice? -- Trauma-informed assessment -- Sensory-based, trauma-informed assessment -- Establishing safety through self-regulation -- Creating and sustaining trauma-informed environments -- Trauma-informed relationships -- Supporting resilience and posttraumatic growth -- Trauma integration.
Includes bibliographical references (p. 217-233) and index.
Keywords: Post-traumatic stress disorder in adolescence -- Treatment; Post-traumatic stress disorder in children -- Treatment; Child psychotherapy; Stress Disorders, Traumatic -- therapy; Adolescent; Child; Crisis Intervention; Psychotherapy -- methods; Resilience, Psychological; Survivors -- psychology